HAEMOLYSIS WITH ANTI-MALARIAL DRUGS IN GLUCOSE 6 PHOSPHATE DEHYDROGENASE DEFICIENCY - Ashish, Bhalla (Journal of Ayub Medical College Abbottabad, 2004)
Development of haemolysis in any febrile patient is a cause of concern for a physician. However with careful history and examination the underlying cause can be detected. The wide spread empirical use of anti-malarial drugs and NSAIDs in febrile patients can result in haemolysis in susceptible population. G6PD deficiency leads to haemolysis in patients whenever they are exposed to oxidative stress in the form of drugs. There is a long list of drugs, which can cause this dreadful complication and serious problems for the patients. These drugs are to be avoided in G6PD deficient patients but it is difficult to anticipate this complication. Since it is difficult to predict which patient might develop this complication when drugs like NSAIDs and anti-malarial drugs are used in febrile patients, it is important to be careful while using these drugs in susceptible population. Key words: G6PD, anti-malarial drugs, haemolysis